A comparative study of various types of intravenous fluids on the changes during induction of general anaesthesia - Kumar, Surendra; Singh, Desh Pal; Sharma, Shailja; Kumar, Praveen (International Surgery Journal, 2019)
Background: The induction and endotracheal intubation is the most risky and initial process of general anaesthesia. Without induction and endotracheal tube placement one cannot imagine the general anaesthesia. Propofol and fentanyl are the commonly used drugs for induction of general anaesthesia. These drugs produce hypotension and other cardiorespiratory disturbances. These hazardous and sometimes fatal effects can be reduced and eliminated by preloading the patients with colloid or crystalloid solutions. Methods: We selected 90 patients who visited our hospital in the last 2 years from June 2017 to May 2019. All the investigations and pre-anaesthetic check-up was done routinely. These patients had to undergo different surgical procedures under general anaesthesia. The induction of anaesthesia was done with propofol and fentanyl. These patients were divided in three groups A, B and C. Group A patients did not receive any preloading. Group B was given colloids (3.5% gelatins) and group C received crystalloids (Ringer’s lactate solution). The haemodynamic changes were noted and analysed statistically. Results: The study showed that IV fluids given before induction of general anaesthesia blunts the adverse cardiovascular response. Conclusions: We concluded that preload with fluids whether colloids or crystalloids are beneficial to counter the detrimental effects of propofol and fentanyl for induction of general anaesthesia. The preload fluids stabilise the patient haemodynamically. When compared the two, colloids were better to blunt the cardiovascular changes.